RESOURCES AND CAPABILITIES OF FISHERMEN IN AMBON: WHAT LEADS TO COMPETITIVE ADVANTAGE? - Gainau, Paskanova Christi; Kilay, Trisye Natalia; Bonara, Ribka Shintia (Pattimura University, 2023)
Introduction/main objectives: One of sectors massively contributing in the economy of Ambon city is fishery and marine. Nevertheless, fishermen, who have important roles in the business of catching and marketing fishes in markets, relatively live in poverty despite their daily efforts. This study aims to investigate how fishermen utilize resources and capabilities to sail. Background Problems: enormous fish demands in Ambon city should be the point of advantages for fishermen. Further, these requests are because the main consumption of the people of Ambon city is fish. Novelty: This research pictures fishermen lives through economic aspects widely to guideline in exploiting the benefits of fish sales. This situation encourages researchers to find out how fishermen achieve competitive excellence in their businesses. Research Methods: this study employs mixed method approaches through questionnaires, intensive interviews, and observation towards fishermen in the villages of Eri, Air Louw, Latuhalat, and Seri. Data were analyzed with SPSS 17. Findings/Results: Study findings indicate that resources and capability of fishermen significantly influence their competitiveness. The greater their competences are, the higher the selling rates are, and within a long term their eagerness will develop. Conclusion: the more excellent resources used in sailing are, the better fishermen’s keenness is. The more their capabilities are, the higher marketing rates are, and within long period of time their ambitions will improve. Small profits are induced by insufficient fishing tools and equipment used compared with fishermen from different regions. Moreover, poor bargaining position of fishermen compared with bidders in markets eliminates their controls to determine market selling prices. The implication is local government must organize policy focusing on increasing fishermen’s resources and capabilities. Furthermore, regulations are required to fix fish values in open markets to give controls to fishermen. In long term, fishers do not only focus on consumption needs but also on allocation of savings and investments